2022
DOI: 10.21203/rs.3.rs-1834126/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Management of post-traumatic stress disorder symptoms by yoga: an overview

Abstract: Background: Posttraumatic stress disorder (PTSD) can occur after facing with trauma. While PTSD management strategies include first-line pharmacotherapy and psychotherapy, mind-body therapies, such as yoga, are applied in PTSD population. This overview aimed to summarize the effectiveness of yoga interventions on PTSD symptoms in adults in a systematic review including randomized controlled trials (RCTs).Method: We searched for systematic reviews with or without meta-analysis of RCTs involving adults with PTSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…Neuroestimulação em circuito fechado pode contribuir para a normalização da circuitaria cerebral alterada no TEPT. Laplaud et al, (2023) Revisão sobre os benefícios do yoga para sintomas de TEPT, destacando a necessidade de estudos específicos e programas de yoga adaptados.…”
Section: Metodologiaunclassified
“…Neuroestimulação em circuito fechado pode contribuir para a normalização da circuitaria cerebral alterada no TEPT. Laplaud et al, (2023) Revisão sobre os benefícios do yoga para sintomas de TEPT, destacando a necessidade de estudos específicos e programas de yoga adaptados.…”
Section: Metodologiaunclassified
“…26,27 Tailored practice of trauma-sensitive yoga by people with PTSD has been suggested to reduce PTSD, depression and anxiety symptoms. 28 A recent overview of reviews concluded effectiveness of yoga for PTSD symptoms, 29 possibly through the meditation component reducing intrusive thoughts and balancing physiological arousal. 30 The number of clinical trials on exercise, regular physical activity and mind-body exercises for PTSD is growing.…”
Section: Introductionmentioning
confidence: 99%